2019
DOI: 10.1002/ange.201906327
|View full text |Cite
|
Sign up to set email alerts
|

N2O Reductase Activity of a [Cu4S] Cluster in the 4CuI Redox State Modulated by Hydrogen Bond Donors and Proton Relays in the Secondary Coordination Sphere

Abstract: The model complex [Cu4(μ4‐S)(dppa)4]2+ (1, dppa=μ2‐(Ph2P)2NH) has N2O reductase activity in methanol solvent, mediating 2 H+/2 e− reduction of N2O to N2+H2O in the presence of an exogenous electron donor (CoCp2). A stoichiometric product with two deprotonated dppa ligands was characterized, indicating a key role of second‐sphere N−H residues as proton donors during N2O reduction. The activity of 1 towards N2O was suppressed in solvents that are unable to provide hydrogen bonding to the second‐sphere N−H groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In a recent work by Mankad, ligands of dppa (μ 2 -(Ph 2 P) 2 NH) with potential proton delivery capability were designed in the preparation of the [Cu 4 (μ 4 -S)(dppa) 4 ] 2+ cluster. 446 The model cluster exhibited N 2 O reductase activity in the presence of hydrogen bond molecules such as methanol, while its catalytic activity was heavily suppressed in solvents without hydrogen bonding sites. Mechanism studies from both structural and computational data suggested that the second-sphere hydrogen bonding induced structural distortion of the [Cu 4 S] active site, therefore enhancing the ability of binding and activating N 2 O.…”
Section: Activating Substrates Bymentioning
confidence: 99%
“…In a recent work by Mankad, ligands of dppa (μ 2 -(Ph 2 P) 2 NH) with potential proton delivery capability were designed in the preparation of the [Cu 4 (μ 4 -S)(dppa) 4 ] 2+ cluster. 446 The model cluster exhibited N 2 O reductase activity in the presence of hydrogen bond molecules such as methanol, while its catalytic activity was heavily suppressed in solvents without hydrogen bonding sites. Mechanism studies from both structural and computational data suggested that the second-sphere hydrogen bonding induced structural distortion of the [Cu 4 S] active site, therefore enhancing the ability of binding and activating N 2 O.…”
Section: Activating Substrates Bymentioning
confidence: 99%
“…12,13 A topologically similar Cu 4 S compound with charge-neutral, amine-bridged bis(phosphine) ligands has also been described as supporting N 2 O reduction but without preservation of the Cu 4 S core composition. 14,15 Somewhat earlier, the Tolman laboratory reported a mixedvalent tricopper compound featuring a disulfide ligand in a μ 3η 2 ,η 1 -S,η 1 ,S′ bridging motif that was also competent to reduce N 2 O to N 2 (Figure 2b). 16 Other small-molecule copper complexes that have been devised as N 2 O active site models have been reviewed by Mankad.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14,132.20,128.78,125.76,125.15,122.11,54.46,42.59. 2,8,3.1.1 3,7 .1 9,13 ]heneicosa-1-( 19), 3,5,7(21), 9,11,13(20), 15,6,12,18-Tris(Nmethylamine), 10, and 2,8,14,15-Tetrathiatetracyclo-[14.3.1.1 3,7 .1 9,13 ]docosa-1 (20), 3,5,7(22), 9,11,13(21),16,18nonaene, 6,12,19-Tri(N-methylamine)-, 11. A portion of 2-(methylamino)benzenethiol was dissolved in MeCN and stirred overnight in the open air to produce 2,2′-disulfanediylbis(N-methylaniline), 9.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mankad reported several [Cu clusters which have N 2 O reductase activities, opening the door for these bioinspired Cu clusters to their practical application in the conversion of greenhouse gases. 13,14 In addition, the known Cu clusters usually consist of Cu I centers which are generally sensitive to oxidation, making them easily agglomeration and deactivate during the catalytic process. 15 Thus, the catalytic potential of most Cu clusters has been severely limited by their low stabilities.…”
mentioning
confidence: 99%